Continuous Brain Activity in Artistic Research I Sit and Worry About Her - Jasna Jovićević (INSAM)
This text discusses the intentions and outputs of the complex creative processes associated with a sound experiment entitled I Sit and Worry about Her. This project involves a sound representation of the continuous motherly worries within the wider context of artistic research, by analyzing and measuring the brain activity as a central concept of the work. The project explored the applications of electroencephalogram technology (EEG) in order to deepen the practice of musical perception and creation, but also to present an affective mother-daughter relationship I explored the spontaneous interactive relations of the participants during musical improvisation. The results of this research were presented in the form of a musical performance.